Textuality and Contextuality in the Interpretation of the Qur'an: An Integrative Hermeneutical Approach to Contemporary Social Relevance - Nurhuda, Abid; Hariyadi, Muhammad; Lathif, Nur Muhammad (Baca Dulu Publisher, 2025)
This study discusses the epistemological dynamics between textuality and contextuality in the interpretation of the Qur'an, a classic yet still relevant theme in the field of tafsir studies. The paradigm difference between textual and contextual exegetes illustrates two major currents of Islamic thought: one emphasizes the integrity of the text as absolute divine revelation, while the other seeks to present the message of the Qur'an in an ever-changing social context. This study uses a qualitative approach with a literature review method, supported by integrative hermeneutic analysis that combines Fazlur Rahman's double movement theory, al-Syatibi's maqaṣid al-shari‘ah, and Abdullah Saeed's ideas on contextualizing the Qur'an. The results of the study show that the textual-contextual dichotomy is actually illusory: the two must be combined so that interpretation remains faithful to divine meaning while being responsive to human reality. This integration gives rise to a transformative interpretation paradigm that is relevant to the challenges of religion, social ethics, and national life today. Thus, the interpretation of the Qur'an does not stop at theological understanding but develops into a social praxis that fosters justice, moderation, and universal humanity.